Sistema de geração e armazenamento de energia elétrica utilizando transdutor piezelétrico na forma pulsada - Sanches, Fabricio Marqui [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper investigated the energy viability of the use of piezoelectric buzzers, rectifier circuit full-wave and DC-DC-converter in a power harvesting systems subjected to mechanical stress caused by the traffic of vehicles and / or walk for pedestrians, demonstrating the possibility of re-use of energy in charging batteries to power autonomous monitoring circuits, display, illumination, etc., in remote locations, eliminating or extending the intervals needed between charges these devices. The piezoelectric generator is analyzed through excitation carried out by a pneumatic cylinder simulator electronically controlled impacts with a frequency of 0.5 Hz and 1 Hz, containing different amounts of PZTs (2, 4, 8) and connection configuration (parallel or serial) . The extracted results are related to the voltage, current, power and energy stored in function of time, still being made relations of these quantities for the number of PZTs, area they occupy, force and pressure applied on them. At the end we can conclude the feasibility of using simple devices in power harvesting systems to generate energy through excitations in pulsed manner and at low frequencies, with higher values in the circuit output in terms of power and current to voltage 5 volts, 108 µW and 21,5 µA (0,53 Kg and 0,83 N/cm2), just like 118,8 µW and 23,6 µA to (2,13 Kg e 3,33 N/cm2), obtained with 8 PZTs, connected in parallel and excited to 1 Hz.

Neste trabalho é investigada a viabilidade energética do emprego de buzzers piezelétricos, circuito retificador de onda completa e conversor DC-DC elevador em um sistemas de power harvesting submetido a esforços mecânicos causados pelo tráfego de veículos e/ou caminhar de pedestres, demonstrando a possibilidade de reutilização dessa energia no carregamento de baterias para alimentação de circuitos autônomos de monitoramento, indicação, iluminação, etc., em locais remotos, eliminando ou estendendo os intervalos necessário entre as recargas desses dispositivos. O gerador piezelétrico é analisado mediante a excitação realizada por um cilindro pneumático simulador de impactos controlado eletronicamente com frequência de 0,5 Hz e 1 Hz, contendo diferentes quantidades de PZTs (2, 4 e 8) e configuração de ligação (série ou paralelo). Os resultados extraídos são referentes à tensão elétrica, corrente, potência e energia armazenada em função do tempo, sendo ainda feitas relações dessas grandezas com diferentes números de PZTs, área que ocupam, força e pressão aplicada sobre os mesmos. Ao final pode-se concluir a viabilidade da utilização de dispositivos simples em sistemas de power harvesting para geração de energia através de excitações na forma pulsada e em baixas frequências, sendo os maiores valores na saída do circuito em termos de potência e corrente para tensão de 5 volts, 108 µW e 21,5 µA (0,53 Kg e 0,83 N/cm2), bem como 118,8 µW e 23,6 µA para (2,13 Kg e 3,33 N/cm2), obtidos com 8 PZTs, conectados em paralelo e excitados a 1 Hz.
Generation system and electric energy storage using piezoelectric transducer in pulsed operation
Keywords: Power harvesting; Conversor boost; Piezoelectric materials; Piezoelectric buzzer in pulsed operation; Boost converter; Materiais piezelétricos; Buzzer piezelétrico na forma pulsada